Managing Diabetes: The Need for Support - Ramraj, Udhavana; Govender , Nalini; Poovendhree Reddy, Settings; Bhagwan , Raisuyah (Universitas Negeri Semarang, 2024)
Background: This study aimed to determine the psychosocial aspects of diabetes management and treatment. Methods: A qualitative research method was used to guide this study. The study population was diabetic patients over the age of 50 years. A semi-structured interview was used to obtain data, which was transcribed and coded and later developed into themes. Results: Five broad themes emerged from the analyses, viz., patient understanding of diabetes, psychological effects, the impact of diabetes on life, experiences of support, and treatment and management of diabetes. Conclusion: The findings from this study highlight the personal health and social strain of diabetes, as well as the challenges experienced in terms of the stress and anxieties associated with the disease